2022
DOI: 10.1002/ansa.202100042
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman analysis of intracellular vitamin B12 analogs in methanogenic archaea

Abstract: Methanogenic archaea (methanogens) are microorganisms that can synthesize methane. They are found in diverse environments ranging from paddy fields to animal digestive tracts to deep‐sea hydrothermal vents. Investigating their distribution and physiological activity is crucial for the detailed analysis of the dynamics of greenhouse gas generation and the search for the environmental limits of life. In methanogens, cobamide cofactors (vitamin B12 analogs) play a key role in methane synthesis and carbon fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Moreover, our other work also demonstrated that one Baizosediminiarchaeum species of the lignin-degrading clade employs a novel MT system to transfer the methyl groups from lignin-derived ArOCH 3 to H 4 MPT, which are either further oxidized to CO 2 or converted to acetate for energy production ( 45 ). This suggests that this Bathyarchaeia-specific MT system plays a key role in anaerobic lignin degradation, thus likely explaining their predominance in the lignin-enriched estuarine and nearshore sediments.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, our other work also demonstrated that one Baizosediminiarchaeum species of the lignin-degrading clade employs a novel MT system to transfer the methyl groups from lignin-derived ArOCH 3 to H 4 MPT, which are either further oxidized to CO 2 or converted to acetate for energy production ( 45 ). This suggests that this Bathyarchaeia-specific MT system plays a key role in anaerobic lignin degradation, thus likely explaining their predominance in the lignin-enriched estuarine and nearshore sediments.…”
Section: Resultsmentioning
confidence: 98%
“…Accordingly, the presence of the cobalamin synthesis pathway in these two genera makes Bathyarchaeia the third archaeal lineage with this unusual capability, suggesting they could serve as a keystone species in the subseafloor microbial community by providing this essential cofactor for other members. In addition, some Baizosediminiarchaeum species could grow with lignin as the energy source ( 14 ) using a novel O-demethylation methyltransferase system that require cobalamin-binding corrinoid protein ( 45 ), while the growth of certain Baizomonas species (assigned to subgroup-6) was also significantly simulated by different lignin-derived aldehydes with methoxy groups in enrichments ( 15 ). Overall, the cobalamin synthesis capability might be one of the key factors in explaining the ubiquitous distribution and predominance of genera Baizomonas and Baizosediminiarchaeum (previously subgroups-6/-5bb and -8), even the whole class Bathyarchaeia, in global freshwater and marine sediments ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…S5). Despite cobalamin being an essential cobalt-containing cofactor for all three domains of life, in the domain Archaea, only a few Thaumarchaeota and euryarchaeotal methanogens could de novo synthesize it, which might facilitate their key roles in seawater and the methane zone in deep sediments, respectively ( 36 , 37 ). Accordingly, the presence of the cobalamin synthesis pathway in these two genera makes Bathyarchaeia the third archaeal lineage with this unusual capability.…”
Section: Resultsmentioning
confidence: 99%